The role of leadership in hospitality industry in the Moses Kotane local municipality - Mohono, Sebonta Francinah Desbo (My University, 2017)
The research focuses on the function of leadership in the hospitality industry in Moses Kotane Local Municipality, how over years they allowed the industry to be at its lowest point. Worldwide the hospitality industry sustains an ongoing need for managers at all levels, the need is even greater for managers who can cultivate the long –term mind-set, capabilities and skills of a greater leader. Not every manager has the skills to become a hospitality leader, but managers who can grow into that mantle are instrumental in driving long term business success. It is the author’s intention to further understand from the perspective of the industry leaders in Moses Kotane, labour, tourism consumers and community as to how they in their own words explain the tourism and hospitality experience informed by the leader’s best practices and how this impact in their environment explained in their own words.
A research report submitted to the faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management (in the field of Public and Development Management). 2017
Keywords: Hospitals--South Africa--Administration; Leadership; Hospitals--South Africa--Administration